ENVIRONMENTAL DISCLOSURE PRACTICES: A NEO INSTITUTIONAL THEORY PERSPECTIVE ACROSS INDUSTRIES - Sayuti, Alfian; Prasetyo, Rahman (Lembaga Penerbitan Unversitas Esa Unggul, 2024)
Environmental issues have been one of the topics discussed at international conferences since Stockholm 1972 to Stockholm 2022. Indonesia is participating in the improvement of sustainability performance, so the creation of regulations and policies related to environmental issues is necessary for companies operating in Indonesia. This research examines environmental disclosure based on industry type (model 1) and examines environmental disclosure before and after the issuance of regulations related to sustainability reporting (model 2). The data used are mining and manufacturing companies listed on the Indonesia Stock Exchange in 2020-2021. The results of the study prove that there are differences in environmental risks between mining, high-profile and low-profile manufacturers. Furthermore, there are differences in environmental disclosure scores before and after the issuance of these regulations. These findings enhance the Neo-Institutional theory that regulators can exert pressure on an institution.